Analisis Kandungan Mie Tinggi Serat Substitusi Tepung Kulit Buah Naga dan Tepung Bekatul - Feni Ulfi Susanti; Dwi Kurnia PS (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Diabetes mellitus is a chronic metabolic disease or disorder with multiple etiologies characterized by high blood sugar levels accompanied by impaired carbohydrate, lipid and protein metabolism as a result of insulin function insufficiency. Therefore, alternative high-fiber foods are needed. One of them is by providing alternative foods in the form of noodles substituted with dragon fruit peel flour and bran flour. This study aims to determine the macronutrient content and acceptability of noodles as an alternative high-fiber food. This study used the True Experimental Design method with a Completely Randomized Design (CRD) with 4 levels of dragon fruit peel flour and bran flour substitution treatment, namely P0 (100:0:0), P1 (0:75:25), P2 (0:50:50) and P3 (0:25:75). The results showed that there was an effect on noodles substituting dragon fruit peel flour and bran flour showing an effect on the levels of calories, protein, fat, carbohydrates, ash, water, fiber, and acceptability in the categories of color, taste, aroma and texture in noodles. increased fiber content in noodles, with the highest fiber content in treatment P3. The conclusion of this study is that the addition of dragon fruit skin flour and rice bran flour in larger amounts produces noodles with a slightly bitter taste and a rancid aroma.